Ocular manifestations of congenital insensitivity to pain: a long-term follow-up. Issue 9 (22nd March 2021) - Elsana, Baker; Gradstein, Libe; Imtirat, Ahed; Yagev, Ronit; Barrett, Chiya; Ling, Galina; Abu Tailakh, Muhammad; Baidousi, Amjad; Tsumi, Erez
Abstract : Aim: To describe ocular manifestations in children with congenital insensitivity to pain with and without anhidrosis (CIPA and CIP). Methods: We reviewed records of eye examinations of 39 children diagnosed with CIPA or CIP. We collected clinical data, with particular attention to ocular surface findings. Corneal sensitivity was tested by presence of a blink reflex upon touching the cornea. Statistical analysis assessed differences in manifestations between the two conditions, and relationships among corneal sensitivity, presence of corneal opacities and visual acuity (VA). Results: CIPA was diagnosed in 32 children and CIP in 7. The median follow-up periods were 50 months (CIPA group) and 94 months (CIP group). Corneal opacities were present in 23% of CIPA eyes and in 57% of CIP eyes. A blink reflex was positive in 52% of CIPA eyes and in 33% of CIP eyes. We recorded VA ≥20/25 in 36% of CIPA eyes, whereas all patients with CIP had VA ≤20/30. For the whole cohort, we found a negative correlation between a preserved blink reflex and the presence of corneal opacities, and a positive correlation between a preserved blink reflex and VA ≥20/25. Conclusion: Children with congenital insensitivity to pain are prone to develop corneal scarring. Patients with CIP tend to have more severe ocular surface disease than those with CIPA, probably due to more prevalent loss of corneal sensation. In both groups, a preserved blink reflex correlated with good vision. Affected children should have close follow-up to promptly treat ocular surface disease and prevent vision loss.